2010
DOI: 10.1590/s0104-42302010000300026
|View full text |Cite
|
Sign up to set email alerts
|

Novos conhecimentos sobre a flora bacteriana vaginal

Abstract: The aim of this review is to update knowledge about the vaginal ecosystem, emphasizing non-cultivation methods for bacterial identification (gene amplification), the several Lactobacillus species that comprise normal vaginal flora and influence of host genetics on bacterial interactions with local innate and acquired immune defenses. A Medline (Pubmed) search from 1997-2009 for relevant articles was performed and the most informative articles were selected. The use of non-cultivable techniques (genes amplifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
19

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 35 publications
0
18
0
19
Order By: Relevance
“…A study of multinational populations showed that L. crispatus was the most commonly predominant species in most populations (Pavlova et al, 2002). The association between geographical area and Lactobacillus species may be partly explained by genetic factors, because the genetic capacity to produce antimicrobial factors could affect vaginal bacteria including Lactobacillus species (Linhares et al, 2010). In addition, diet may influence the Lactobacillus species in the intestinal tract and the vagina (Lamont et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…A study of multinational populations showed that L. crispatus was the most commonly predominant species in most populations (Pavlova et al, 2002). The association between geographical area and Lactobacillus species may be partly explained by genetic factors, because the genetic capacity to produce antimicrobial factors could affect vaginal bacteria including Lactobacillus species (Linhares et al, 2010). In addition, diet may influence the Lactobacillus species in the intestinal tract and the vagina (Lamont et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Research using culture-based methods among women living mostly in industrialized countries first suggested that a healthy vaginal flora was dominated by four species: L. fermentum; L. brevis; L. jensenii; and L. casei (Antonio et al, 1999). More recently, studies using molecular methods in similar populations have narrowed the predominant species seen in the vaginal mucosa of most reproductive age women to L. crispatus, L. iners and L. gasseri (Linhares et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Por outro lado, Lactobacillus sp é a espécie dominante na microbiota vaginal; estudos recentes apontam que, em algumas mulheres, microbiota vaginal não dominada por esse microrganismo pode ser normal e não necessariamente patogênica (15) .…”
Section: Epitéliounclassified